Allelopathic effects for three plants extracts on weeds of wheat (Triticum aestivum L.) - Awni Abdalbaki, Hussein Ali Salim, Abdalsalam; Balkees Reski and Wissam Kahtan Alwan, Hussein Ali Khalid ,Hana Safi Eshak, (Journal of Medicinal Herbs and Ethnomedicine)
An investigation was carried out to evaluate the allelopathic effects of aqueous extracts of Eucalyptus obligo, Chrysanthemum indicum and Eruca sativa on weeds of wheat in the research field of Kanan region, province of Diyala, Iraq during 2016-2017. A minimum number of weeds and Dry weight of weeds were significantly recorded (3.3 m-2, 15 g) respectively in Eruca sativa extract while maximum control of weeds % and inhibition of weeds % (71.2, 87.5%) were significantly recorded in Eruca sativa extract. Different yield components of wheat, such as crop height and 1000-grain weight showed maximum significantly difference 109.0 cm and 42.9 g respectively in Eucalyptus obligo whereas spike length, number of grains / spike, number of plants / m2 and grain yield revealed maximum significantly difference 11.8 cm, 52.6, 341and 1568 g respectively in Chrysanthemum indicum.